Use of Pharmacological Facilities for the Prophylaxis of Diseases of Human in Antarctic - Y. V. Moiseyenko (Ukrainian Antarctic Journal, 2010)
Explored the mechanisms of violations of adaptation of man in Antarctic. 97 persons are inspected (men in age 22-45 years). For researches technologies of registration of parameters of psychoemochen functions, breathing, circulation of blood, blood were used. The main links ofprocesses of dysregulation are certain in the functional systems of organism. On the results of researches pathogenethyc directions were built for the choice of adequate pharmacological facilities of correction of û prophylaxis of pathology.